The Dynamics of Human Character Development from the Perspective of Ar-Razi - Azizah G. Justusia (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The experiences humans encounter throughout life shape their character and behavior toward their surroundings. Human development from birth continuously undergoes dynamic changes, both physically and mentally. This issue also concerned Ar-Razi, who sought to explore the dynamics of the human psyche while remaining grounded in Islamic principles and scientific knowledge. He introduced a theory of character development consisting of four phases: (1) the age of growth, (2) adolescence, (3) middle age, and (4) old age. Ar-Razi also classified levels of the soul based on his interpretation of Surah Al-Kawthar into three stages: (1) the highest level, in which the heart and soul are immersed in the light of Allah; (2) the second level, characterized by devotion to Allah through various forms of physical worship; and (3) the third level, the lowest degree, which is oriented toward worldly matters. This article aims to explore Ar-Razi’s theory of development holistically.